Analisis Strategi Bermain Peran Terhadap Kemampuan Berbicara Siswa di Kelas XI Madrasah Aliyah Ponpes Tahfidz Al-Faiz Tembung - Ade Alawiyah Lubis; Faridah Faridah; Rina Devianty (Fonologi: Jurnal Ilmuan Bahasa dan Sastra Inggris, 2025)
This research, titled "Analysis of Role-Playing Strategies on Students' Speaking Skills in Grade XI of Madrasah Aliyah Ponpes Tahfidz Al-Faiz Tembung," is motivated by the students' learning outcomes that show limitations in speaking skills in Indonesian language subjects. Learning activities that take place in the classroom are often limited to listening and lecturing activities, even though the curriculum demands that students have higher-order thinking (HOT) skills such as analysis and discussion. This research uses a qualitative descriptive approach with research subjects consisting of teachers and students. Data collection was carried out through observation, interview, and documentation techniques. This research aims to analyze: (1) the implementation of role-playing strategies in improving students' speaking skills, (2) the assessment of Indonesian language learning outcomes using this strategy, and (3) the supporting and inhibiting factors in using role-playing strategies. The results of the research show that the implementation of learning with role-playing strategies successfully increased students' competence and learning activity, especially in channeling ideas and opinions. The main supporting factors include teacher involvement, students' mastery of the material, and the use of relevant textbooks, including drama scripts and performance videos. Conversely, the inhibiting factors are students' shyness when role-playing and lack of mastery of the material. Based on the findings of this research, role-playing strategies are suitable to be implemented by teachers as a solution to improve the quality of learning in Indonesian language subjects.